2015
DOI: 10.1111/echo.13132
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Longitudinal and Circumferential Layer‐Specific Myocardial Strains and Their Determinants in Healthy Subjects

Abstract: Three-layer analysis of longitudinal and circumferential strain using two-dimensional speckle tracking imaging (2DSTI) can be performed on a clinical basis and may become an important method for the assessment of real time, quantitative global, and regional LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
61
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 20 publications
10
61
1
1
Order By: Relevance
“…An increased epicardial-to-endocardial gradient of LS were described from the basal to the apical level of the ventricle in pregnant women, which is in agreement with the findings of layer-specific LS in normal non-pregnant subjects [7, 9]. We noticed that the deformation of three-layer myocardium at the basal level was significantly different in the second and the third trimester, while it was almost homogenous in the early pregnancy and postpartum as well as non-pregnant controls.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…An increased epicardial-to-endocardial gradient of LS were described from the basal to the apical level of the ventricle in pregnant women, which is in agreement with the findings of layer-specific LS in normal non-pregnant subjects [7, 9]. We noticed that the deformation of three-layer myocardium at the basal level was significantly different in the second and the third trimester, while it was almost homogenous in the early pregnancy and postpartum as well as non-pregnant controls.…”
Section: Discussionsupporting
confidence: 83%
“…Until recently, speckle tracking echocardiography (STE) has been upgraded, which allows to quantify myocardial function in three layers [6]. Layer-specific differences of myocardial performance and deformation have been analyzed in normal subjects and different heart diseases [69]. However, still little is known about how differently multilayer myocardium contributes to myocardial deformation throughout the progress of normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the transmural gradient may be a unique parameter of myocardial diseases. In an echocardiography-based study, transmural strain gradient was established as a new parameter to evaluate wall motion, and was considered to be a more robust parameter of strain than global strain34. Therefore, in the present study, a parameter named G epi-endo in Ecc was also calculated, which showed an interesting association with age.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the endocardial layer moves toward the chambers of the heart, its movement range is larger than the range of the epicardial layer which is still in a relatively static condition during the myocardial systolic phase, which causes different local stresses in each layer . Some studies of GLS and GCS by layer‐specific 2DSTE on healthy people had similar gradient characteristics …”
Section: Discussionmentioning
confidence: 99%